Allelopathic Effect of West Java Local Black Rice Varieties on Barnyard Grass (Echinochloa crus-galli (L.) Beauv.) at Germination Stage - Kadapi*, Muhamad; Sobardini, Denny; Helena, Elissa; Hanindianingrum, Haritsa; Noor, Fachryansah; Wicaksana, Noladhi; Sumadi (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2021)
Some colored rice varieties are able to release root exudates that contained allelochemicals which can inhibit the growth of other plant species including weeds. This capability is required if rice is to compete with weeds from the germination stage onwards. One of the dominant weeds in rice fields is barnyard grass, which can have negative effects on rice growth at every stage, particularly at the germination stage. Therefore, the objective of this study was to evaluate the response of local black rice varieties originated from West Java, Indonesia against barnyard grass at the germination stage. İn this study, four local black rice varieties that originated in three West Java districts, two from Subang (SB and SB II), one from Sukabumi (SMI) and one from Tasikmalaya (TSK), were sowed together with Echinochola cruss-gali in petri dishes with six replications. The experiment was conducted in a plant breeding and seed technology laboratory in order to observe T50, germination percentage, vigour index, shoot and root length at 7 and 14 days after sowing (DAS). The results showed that the four local black rice cultivars had allelopathic potential, as indicated by vigour traits at germination stages of barnyard grass. Besides, the presecense of barnyard grass showed an inhibitory or stimulatory effect on black rice growth in its early germination stage (7 DAS). However, the local black rice that originated from Subang (SB II) showed growth recovery and inhibitory effect towards barnyard grass at the second germination stage (14 DAS), as measured by vigour index, shoot length and inhibitory percentage. This study suggested that the ability to recover at the second stages of germination is a useful trait to be considered when conducting breeding program for the efficiency of weed management. Keywords: allelochemical; tolerance; variation; black rice; weed *Corresponding author: Tel.: (+62) 8812279027 E-mail: kadapi@unpad.ac.id